VAXI vaccine taxi : a cold carrier system for vaccine transport that can prevent vaccine wastage in remote, 5th class municipalities in the Philippines - Carstensen, Marichu Liwag; de la Peña, Fortunato Jr. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2016)
Vaccine wastage is one of the biggest problems of immunization programs all over the world. The WHO once reported 50% wastage worldwide. The cold chain logistics demands a 2-8 °C temperature range from the manufacture all the way to the end user. Vaccines should not be frozen or exposed to heat and light. After a review of the current carriers and a search for the weakest link in the cold chain, a lot of loopholes that cause spoilage were observed. Three different session sites, including a remote municipality with only 12 hours of power everyday, were studied. Interviews with the health workers involved were done. Survey results showed the environmental challenges that users encounter in their work and the difficulties that they are having with the existing carriers. VAXI is a cold carrier system that solves most of the problems that hamper vaccination programs. The reconfigured parts, added features and accessories make it a viable product that may help reduce vaccine wastage in remote places. The carrier system lessens the burden on the frontline health workers from whom much is expected but less is given
Thesis (Bachelor of Fine Arts - Industrial Design)--University of the Philippines Diliman
Bibliography : leaves 77-82.
Keywords: Vaccines -- Storage